Communication and evaluation of science: landmarks and recent scientific results - Torres-Salinas, Daniel (Anuario ThinkEPI, 2010)
A review of the major developments in the field of scientific communication and research evaluation in 2009 is divided into three themes. The first is devoted to scientific communication on the internet, focusing on the use of Twitter in science, Open Access numbers in Spain, and e-science. The second block is devoted to the use of indicators for evaluating scientific activity as proposed in the Mesur project and in the PLoS model for the evaluation of journal articles. Finally we dedicate a block to bibliometrics, highlighting the new rankings of universities in Spain and recent changes in Web of Science and Scopus citation indexes.
Keywords: Scientific communication; Web 2.0; E-Science; Usage indicators; Rankings of universities; Citation indexes.